An Analysis of Problems in Translating Descriptive Text from Indonesian to English by Sixth Semester of English Department Students of Universitas Negeri Padang - Yulisa Aprianti; Havid Ardi (Universitas Negeri Padang, 2023)
Translation might be challenging for some people studying English as a second language. In translation process, many students faced some problems. They do not know what factors cause it. Many factors arise during the Indonesian-to-English translation. The goal of this research is to examine the problems faced by students in translating descriptive texts from Indonesian to English, and the factors that contribute to those problems. A descriptive qualitative method was used in analysis data. Students from the English Department who were in their sixth semester participated in this study. The sample was taken by the using cluster random sampling. Data were collected by using translation test and interview. The result shows that, there are five components to the students' problems during the Indonesian to English translation of descriptive text. Word choice, grammatical. rhetorical, pragmatic, and cultural problems are some of them. The result indicates that there five problems in the students’ translation test that should be anticipated in translation class.